Role of Self-control Moderating on the Influence of FoMO, Lifestyle, and Impulsive Buying on Personal Financial Management (Case of KIP Students at the Faculty of Economics and Business) - Scolastica Kapitan; Maximus L. Taolin; Sarlince Sandy Mauk (International Journal of Financial, Accounting, and Management, 2026)
Purpose: This study examines the impact of Fear of Missing Out (FoMO), lifestyle, and impulsive buying on personal financial management, with self-control as a moderator, in the case of KIP students at the Faculty of Business and Economics. Research Methodology: This study uses quantitative methods through questionnaire distribution. The population in this study comprised 595 active students receiving the Kartu Indonesia Pintar Kuliah (KIP Kuliah)  scholarship from the Faculty of Economics and Business, Timor University. The analysis method used was the Moderated Regression Analysis (MRA) Interaction Test with the Smart PLS 4.0 analysis tool. Results: FoMO, lifestyle, and impulsive buying significantly influenced personal financial management. Self-control, however, did not moderate these relationships, indicating that social pressures, trend-following, and spontaneous shopping tendencies continue to dominate financial behavior despite students’ self-control. Conclusions: Personal financial management is crucial for maintaining financial stability among KIP students at the Faculty of Economics and Business. Social pressures and a consumerist lifestyle must be addressed to ensure that KIP Kuliah FEB utilize their scholarships optimally Limitations: The sample size of the study is not large and extensive, and the number of respondents is only KIP students in one faculty; therefore, the results cannot be generalized widely. Contributions: This study contributes to the growing literature on student financial behavior by highlighting the psychological and social roles of financial management. The findings can also inform campus policymakers' design of financial literacy programs that are more adaptive to the emotional and social challenges students face.